Heterogeneous Sports Participation and Labour Market Outcomes in England - Michael Lechner; Paul Downward (Center for Economic Studies and ifo Institute (CESifo), 2013)
Based on a unique composite dataset measuring heterogeneous sports participation, labour market outcomes and local facilities provision, this paper examines for the first time the association between different types of sports participation on employment and earnings in England. Clear associations between labour market outcomes and sports participation are established through matching estimation whilst controlling for some important confounding factors. The results suggest a link between different types of sports participation to initial access to employment and then higher income opportunities with ageing. However, these vary between the genders and across sports. Specifically, the results suggest that team sports contribute most to employability, but that this varies by age across genders and that outdoor activities contribute most towards higher incomes.
Keywords: I12; I18; J24; L83; C21; 330; sports participation; human capital; labour market; matching estimation